A Rare Dermatologic Disease in Pregnancy: Rosacea Fulminans- Case Report and Review of the Literature - Demir, Omer; Tas, Inci Sema; Gunay, Berrin; Gungor Ugurlucan, Funda (Open Access Macedonian Journal of Medical Sciences, 2018)
BACKGROUND: Rosacea is a common, chronic disorder that can present with a variety of cutaneous or ocular manifestations. Skin involvement primarily affects the central face, with findings such as persistent centrofacial redness, papules, pustules, flushing, telangiectasia, and phymatous skin changes. The pathways that lead to the development of rosacea are not well understood. The relationship of pyoderma faciale (also known as rosacea fulminans) to rosacea also is uncertain. We aimed to write this article with the aim of showing how a pregnant patient who has been aggravated by the degree of lesions on the face during the first trimester of pregnancy is treated and to show what is in the literature in this issue. CASE REPORT: A 22-year-old woman complained of painful erythema, papules and pustules on the face. She had fever and malaise during the sixth week of her first pregnancy and a history of the mild eruption and seborrhea before her pregnancy with flaring over the preceding 4 weeks. Dermatologic examination revealed red erythema of all involved facial areas; the lesions consisted of papules, pustules and nodules. The case was diagnosed as rosacea fulminans (pyoderma faciale) by these findings. In the literature, there are some effective therapeutic options such as retinoids, tetracyclines, antiandrogenic contraceptives, and dapsone and these were not used because they are contraindicated in pregnancy. Amoxicillin-clavulanic acid 1 gr/day, wet compresses, and a fusidic acid cream were started. After the activity of the disease had been suppressed for 10 days, antibiotic was stopped, and the other treatment options were applied topically for the next month. One month after cessation of treatment, the lesions had disappeared with only mild erythema remaining. There was minimally flushing on the face and no telangiectasia. CONCLUSION: In conclusion, there is no substantial evidence as to the mechanism by which pregnancy may trigger this conditioner whether the gender of the fetus influences the development of rosacea fulminans, but is generally accepted that hormonal changes in pregnancy play an important role. The pathogenesis of rosacea fulminans remains uncertain, but it is obvious that the further basic and clinical research is required to optimise the management of this rare facial dermatosis.